PERSEPSI MAHASISWA FISIP UNDIP TERHADAP DEMOKRATISASI DI INDONESIA - Jane Theresia Silaban; Yuwanto .; Lusia Astrika (Journal of Politic and Government Studies, 2013)
In reaching the whole system of democratic government, Indonesia hasundertaken the process of democratization (the transition, consolidation, and maturingpolitical culture community). This background has been made in this study. Problemsthat arise: How do students' perceptions of the Faculty of Social UNDIP aboutdemocratization in Indonesia?The purpose of this study was to describe the perceptions of students FISIPUNDIP about democratization in Indonesia. The data was collected throughquestionnaires with a population of as many as 3083 students of Faculty of SocialUNDIP and total sample of 100 students of Faculty of Social UNDIP. This type ofresearch is descriptive quantitative research.The analysis showed that the democratic system is in conformity with thesystem of government in Indonesia. College students who are part of the public haveconfidence that the ongoing democratization in Indonesia has done well but notconvinced that democratization in Indonesia (with the implementation of thetransition and consolidation) have been able to improve the socio-economicconditions of society and makes government of Indonesia to be better.Recommendations from this study are (i) For the government: provide earlyeducation about the system politic, providing open space for society, more transparentand accountable in the implementation of the system of government. (ii) For thecommunity: makes democracy as a way of life that guides the livelihood of thenation, more caring and actively participate in the political system in Indonesia. (iii)For college students: waged back the fighting spirit in defending the fate of nations,revive its role as an Agent of Change to give change for the people and governmentof Indonesia (by not doing harm to others).Keywords: Perseption, Democratization and College Student